(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Human society consists of both men and women.Irrespective of the nature and form of society and its social structure thewoman has always been its integral and inseparable part. Women constitute thehalf of the world population, yet, they are not treated at par with men in manyaspects of life. Indian women suffer systemic discrimination at every stage,correlated with low female literacy, female infanticide, declining sex ratio,nutritional deprivation throughout the life, unequal employment opportunitiesand reduced access to health care.